A novel electrochemical ammonia–nitrogen sensor based on carbon cloth-supported hierarchical Pt nanosheets-Ni(OH)2 nanosheets nanocomposites. (10th August 2021) - Zhang, Liang; Ding, Jie; Cui, Gaoxiang; Zhao, Chun; Suo, Hui; He, Dong
Highlights: A novel electrochemical sensor was designed for detecting ammonia–nitrogen in water. A hierarchical Pt-Ni(OH)2 -CC electrode was fabricated by in situ growth method. This ammonia–nitrogen sensor exhibited accepted detection performance. The hierarchical self-supported structure enhanced obviously sensing performances. Abstract: Accurate and quick detection of ammonia–nitrogen is significant to protect the water source and conduct the sewage treatment. Design of electrochemical sensor is one of strategies to achieve the detection of ammonia. In this work, Pt nanosheets-Ni(OH)2 nanosheets supported by carbon cloth (Pt-Ni(OH)2 -CC) was successfully fabricated based on the in situ growth route following by hydrothermal reaction and electrochemical deposition. By integrating morphology advantages and structure advantages, the proposed Pt-Ni(OH)2 -CC can be served as a sensitive electrode for detecting aqueous ammonia. After further measured and evaluated detection ability of Pt-Ni(OH)2 -CC electrode, The experiment results showed accepted performances with low detection limit of 0.42 µM. Moreover, this Pt-Ni(OH)2 -CC sensor exhibited good selectivity, reusability, reproducibility and stability. This fabricated senor may broaden the ways of self-supported electrode and ammonia detection in water.